Joget Dangkung Kepulauan Riau, Indonesia: Daripada hiburan kampung nelayan kepada persembahan pentas / Anastasia Wiwik Swastiwi - Anastasia , Wiwik Swastiwi (2017)
People in Riau archipelago mostly live along the coast and live as fisherman, just like their ancestors. These people also inherited their ancestors's traditions, one of them is Joget Dangkung dance. This dance is usually performed in the suburban area as social dance to celebrate Semah Laut ritual, a ritual to ask safety for the fisherman after their big catch. Even though Joget Dangkung is a social dance, it has special dancers and music players. This dance is performed by 4-8 dancers and 4 music players who wear traditional costume. The female dancers wear short kebaya, sarong pelekat or batik with flower motive and sanggul siput (sanggul jonget) with flower ornaments. The male dancers and the music players wear Melayu Cekak Musang clothes with songkok and kain samping. Joget Dangkung dance structure consist of several part : bertabik, dondang sayang, serampang laut, jogi, timang anak and muka rawai. It also has several ritual parts : opening, dondang sayang, tandak and closing. The musical instruments used in this dance performance are gendang tambur, violin, and gong. As time passes, there are social, political, and economical changes which affect these people and those changes also affect Joget Dangkung itself. Joget Dangkung then performed not only as ritual dance, but also as entertaiment for commoners. As an entertainment dance Joget Dangkung undergo several changes in dance structure and musical instrument. As entertainment dance, it focuses only in three parts of the dance, dondang sayang, serampang laut, and jogi. Technological advance causes the use of modern musical instrument in Joget Dangkung performance, now they use keyboard, tamburin and accordion, though not all of them are used. The costume also undergo some changes as the dancer mostly wear the modification of short kebaya, adjusted to the latest model. As well as the music players, they wear Melayu’s Cekak Musang cloth, complete with songkok and saroong.